Implementing and developing cloud computing applications - Sarna, David E. Y. (Boca Raton, Fl. : CRC Press, 2011)
'Major enterprises and small start-ups are beginning to embrace cloud computing for the scalability and reliability that cloud vendors can provide. This book demonstrates how to implement robust and highly scalable cloud computing applications. Filled with comparative charts and decision trees to help navigate the many implementation alternatives, the author describes the major available commercial offerings and guides readers in choosing the best combination of platform, tools, and services for a small, growing start-up or an established enterprise. Aimed at software developers and their managers, the text details cloud development environments, lifecycles, and project management'--
Includes bibliographical references and index.
Keywords: Cloud computing; Business -- Data processing